PENERAPAN METODE QUALITY FUNCTION DEPLOYMENT (QFD) DALAM PENENTUAN PRIORITAS PENINGKATAN KUALITAS LAYANAN RESTORAN PRINGJAJAR - Risenasari, Hepi; Daryanto, Heny Kuswanti Suwarsinah (Forum Agribisnis, 2011)
Restaurant is a kind of service sector which has significant gowth. One of restaurant which has to increase their service quality due to the competitif condition is Pringjajar. The purposes of this research were: 1)Â identify customer needs or WHATs and Technical needs or HOWs ; 2) to analyze implementation of QFD in increasing service quality of Pringjajar. This study conducted on Mei until June 2009. Primary data was collected from 60 consumers and Pringjajarâs management. Quality Function Deployment (QFD) was applied to analyze the evident and compare with RM. Prima. The results show that quality position ofÂ Pringjajar is more than RM. Prima on some atributes. There are some attributes include in the matrix that valued based on competitive requirements, value target customers, sales points, onscale factors of Customer reqirements. Absolute weights of customer reqirements that needs to be prioritized is the comfortable and cleanliness of the room place. For the technical requirements, attributes value based on competitive assessment, value of the target requirements, degree of difficulty is used to calculate the Absolute weights and relatives weights of technical requirements.Â Based on absolute weights of technical requirements, the priority that most need to be improved are ripeninglater service. Based on relatives weights the attributes that should be improved are the same order priority of absolute weights. However, two actions should be improved to increase the serviseÂ quality ofÂ Pringjajar (beginning from first priority) namely (1) improvement of quality of taste ; and (2) improvement of cooking process.